1983
DOI: 10.1111/j.1570-7458.1983.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECOCIOUS METAMORPHOSIS AND MOULTING DEFICIENCIES INDUCED BY AN ANTI‐JH COMPOUND, FMEV IN THE FALL WEBWORM, HYPHANTRIA CUNEA

Abstract: Fluoromevalonate (FMev, ZR‐3516) known as an inhibitor of JH biosynthesis was topically applied in 0.1 to 50 μg/specimen doses to the 3rd, 4th, and 5th instar caterpillars of Hyphantria cunea Drury. The anti‐JH compound induced 3 main types of specific responses: 1) precocious metamorphosis, 2) inhibition of ecdysis, and 3) prolongation of larval development. Precocious pupation was accompanied by behavioural events typical of normal pupation. Third and 4th instar larvae metamorphosed prematurely mostly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…A similar effect of FMev on the fall webworm, Hyphantria cunea Drury, has been demonstrated. 13) Although the mode of anti-JH action of KK-22 is not known, Kuwano et al11) pointed out that the mode of anti-JH action of phenylimidazoles might be different from that of precocenes which are cytotoxic on the corpora allata. In the present experiment with KK-22, precocene I, and II there were some differences among them.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect of FMev on the fall webworm, Hyphantria cunea Drury, has been demonstrated. 13) Although the mode of anti-JH action of KK-22 is not known, Kuwano et al11) pointed out that the mode of anti-JH action of phenylimidazoles might be different from that of precocenes which are cytotoxic on the corpora allata. In the present experiment with KK-22, precocene I, and II there were some differences among them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, precocious metamorphosis had been induced by precocenes in several insects of Diptera, such as the flesh fly Neobellieria bullata [80] and the house fly Musca domestica [36] as well as Lepidoptera, such as the tobacco cutworm Spodoptera litura [81] and P. ricini [31]. Moreover, other anti-JH compounds induced such feature of impaired metamorphosis in various insects, such as Fluoromevalonate (FMev) against the fall webworm Hyphantria cunea [82] and the lawn armyworm Spodoptera mauritia [83]; ETB [65], KK-42 [84,85], KK-22 [86,87] and 3-pyridine derivatives [88] against B. mori. Treatment of N. bullata larvae with KK-110 and J-2710 resulted in precocious pupation [80].…”
Section: Precocious Metamorphosismentioning
confidence: 99%
“…As reported by many studies, larval duration in several insect species (holometabolous or hemimetabolous) had been prolonged as a response to the action of different IGRs, such as the fall armyworm Spodoptera frugiperda as a response to methoxyfenozide (Zarate et al, 2011); S. littoralis as a response to novaluron (Ghoneim et al, 2015) and cyromazine (Tanani et al, 2015); G. pyloalis as a response to lufenuron (Aliabadi et al, 2016); C. pipiens as a response to methoxyfenozide (Hamaidia and Soltani, 2016); C. cephalonica as a response to fenoxycarb (Begum and Qamar, 2016); P. gossypiella as a response to pyriproxyfen (Sabry and Abdou, 2016) and novaluron . Also, treatment of some insects with anti-JH compounds resulted in prolongation of the larval duration, such as 5 th nymphal instar in O. fasciatus after treatment with PI (Bowers and Aldrich, 1980); 4 th instar nymphs of S. gregaria after treatment with PII (Eid et al, 1982); three latter instars of the fall webworm Hyphantria cunea after treatment with fluoromevalonate (Farag and Varjas, 1983); 6 th instar larvae of S. mauritia after treatment with PII (Mathai and Nair, 1984); 5 th instar nymphs of the grasshopper Aiolopus thalassinus after treatment with PIII (Osman, 1988); larval period of S. litura after treatment with PI, PII and ethoxyprecocene (a synthetic analog of P II) (Srivastava and Kumar, 1999); etc. Results of the present study were inconsistent with these reported results, since the topical application of cycloheximide onto the newly moulted last instar larvae of S. littoralis resulted in shortened larval duration, especially at the higher two doses (180 and 120 µg/larva).…”
Section: Affected Developmental Durationsmentioning
confidence: 99%